Use of network technologies in the practice of educational training and re-training of military doctors - Halkina, T. (New Collegium, 2022)
The article defines network technologies that are appropriate to use in the practice of educational training and retraining of military doctors: network technologies for the organization of distance learning, scientific and educational social networks; network technologies supporting the training and retraining of military doctors; digital libraries. It was found that network technology provides a number of new opportunities for creating an open ICT-oriented educational environment for the training and retraining of military doctors. It is specified that the use of network technologies involves compliance with the agreed rules of online behavior: understanding the difference between public online space and personal space; the ability to analyze the meaningful essence of information that is aimed at public distribution, and that is purely personal; ability to critically evaluate information before publication, focus on constructive (positive) "presence" in the network; understanding that any online action can have public feedback; understanding that today the network image is also one’s own reputation.